(3GdeWdY TQM EjSGZhLis - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3GKjQ GdOjf GdGHgQj , GdeaVd Hf YeQ Hf GdeaVd GdGHgQj GdSeQbfOj,J (B663 (3g` s ((3YHjO Gddg CMeO Hf eMeO GdSfhSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi eJY CMHJg HGddWb hGdJhajb hjSQ dge SHd GdJUhQ hGdJUOjb CeG HYO agPG TQM dWja dcJGH GdYdGeI GdCHgQi GdeSei HEjSGZhLi hSejJg GdeWdY s
(3BNQgG (B:s
(3hGdYeOI Ci eG jYJeO Ydjg dgPg GdbjGSGJ gh GdHQgGf dGZjQ dJQcHg ef GdebOeGJ GdjbjfjI hdchfg cGajkG ai EcJSGH GdYdhe GdJUOjbjI hGddg CYde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HBNQgG hbajI HGSe GdTjN eMeO SYjO Hf eMeO Hc EjGS GdOeTbis
(3cJH eJf EjSGZhLi HeOGO CMeQ hcJH GdTQM HeOGO CShO s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdadSaI hGdefWbs